Exploring an infrastructure investment methodology to risk mitigation from rail hazardous materials shipments - Vaezi, Ali (Logistics, supply chain, sustainability and global challenges, 2021)
Railroad is one of the primary modes to transport hazardous materials (hazmat) in North America. For instance, Canadian railroads carried around 50 million tons of hazmat in 2018. Given the inherent danger of trains carrying hazmat, this study aimed at exploring a novel way towards mitigation of the associated risk. This study sought to investigate whether proper rail track infrastructure investment can mitigate the risk from hazmat shipments. To this end, a methodology was developed and then applied to the Canadian railroad network. The proposed three-step methodology captured the differing perspectives of rail carriers and regulatory agencies, and entailed (1) ascertaining the risk-level of various yards and links in the given railroad network, (2) specifying potential candidates for infrastructure investment, and (3) finding the optimum set of investment decisions. The proposed methodology was then applied to the Canadian railroad network to demonstrate that significant risk-reduction can beachieved by adding alternative rail-links around the riskiest locations (i.e. the network hot-spots), and also to show that risk-reduction function is non-linear with non-monotonous behavior. The study showed the possibility of significant hazmat risk reduction through alternative rail-links that could take traffic away from the network hot-spots. The methodology and the resultsfrom the Canadian case can be used by railroad companies and policy makers to estimate the value of potentially risk-reducinginfrastructure investments.
Keywords: hazardous materials; infrastructure investment; infrastrukturne investicije; nevarni materiali; optimizacija; optimization; prometna varnost; railroad network; risk mitigation; transportation safety; zmanjševanje tveganja; železniško omrežje